Impact Of International Trade On Regional Economic Growth - Judijanto, Loso; Azizs , Abdul (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the impact of international trade on regional economic growth through literature studies. International trade is one of the main drivers of economic growth in the era of globalization. Despite a significant increase in the volume of global trade, the distribution of benefits is not always evenly distributed across regions. Some regions with adequate infrastructure access and supportive economic policies experience rapid economic growth, while other less developed regions face limitations in taking advantage of international trade opportunities. This study shows that international trade contributes significantly to increasing Gross Regional Domestic Product (GRDP), investment, and job creation, although these impacts depend on the readiness of infrastructure and the competitiveness of each region. Factors such as government policies and access to global markets also play a role in influencing the benefits obtained. This study recommends policies for infrastructure development and strengthening the competitiveness of local products to ensure that all regions can feel the optimal benefits of international trade. The results of this study provide direction for the government in formulating policies that encourage inclusive and sustainable economic growth at the regional level.